Philippine food industry preferences and uses for dark yellow egg yolk - Zamora, Myrna Benita V.; Azanza, Ma. Patricia V. (2000)
The study aimed to determine food industry preferences and uses for dark yellow hen(Gallus gallus domesticus) egg yolks. The first phase of the study was a survey on preferences and perceptions of food manufacturing industry for egg yolk color. In Phase II, physico-chemical properties of dark yellow were characterized during storage at ambient temperature for 9 d. Dark yolks were produced using corn-soybean basal diet supplemented with canthaxantin. The last phase was on the use of the test yolks in sponge cake and steamed egg custard. Physico-chemical and sensory properties of these products were monitored during refrigeration storage for 6d. Food inductry respondents expressed preference for yellow egg yolk (8.3 ± 2.6 in RYCF) which was associated with freshness and perceived to be typical of hen egg yolk. Although egg vendors are currently supplying the industry with yolks of significantly (p < 0.05) lighter color (7.4 ± 2.4 in RYCF) compared to the preferred, the industry is apparently satisfied. At present, it is very unlikely that the food industry would demand an egg yolk color darker than what they preferred. Canthaxanthin supplementation of hen layer diet at 1.5 g/ton effectively (p<0.05 enhanced raw egg yolk color from 7.82 ± 0.65 in RCYF (yellow) to 10.55 ± 1.56 in RCYF (dark yellow). Rank order of carotenoid concentration in dark yolk was zeaxanthin > lutein > cantaxanthin > other carotenoids. During storage, color of dark yolk significantly (p<0.05) lightened. Results of instrumental color analysis of sponge cake and steamed egg custard established a significant (p<0.05) positive color enhancement upon utilization of dark yolk in the products. However, results of sensory evaluation established that sensory properties of products were not significantly (p>0.05) influenced. Rank order of carotenoid concentrations in both products was similar to raw egg yolk. It is not advisable to pursue canthaxanthin supplementation of hen layer feeds to produce dark yellow for use of the food manufacturing industry. Utilization of dark yolk in sponge cake and steamed egg custard did not impart a perceptible (p<0.05) color enhancement in the products.
Thesis (M.S. Food Science)--University of the Philippines, Diliman
Keywords: Eggs as food; Egg processing -- Philippines; Food industry and trade -- Philippines